Impact of Vitality on Job Performance, Male versus Female: An Empirical Study of the IT Sector of Pakistan - Imran Akbar Saifi; Prof. Dr. Abu Bakar Abdul Hamid; Dr. Waqas Farooq (Journal of Management Practices, Humanities and Social Sciences, 2021)
Vitality is concerned with motivation, opportunity, and engagement. The objectives of this study are first to analyze the relationship between vitality and job performance, and secondly, whether male and female employees differ concerning self-reported vitality and job performance working in the IT sector of Pakistan. Lastly, the impact of vitality on job performance is the same on both genders, or it differs. Data were collected from IT professionals working in different IT-sector companies using a self-administered structured questionnaire. The results identified a significant relationship between vitality and job performance. Self-reported job performance differs for males and females, whereas no difference was found in vitality. The novelty of this study was the impact of vitality on job performance that was different for males and females. The findings of this study have significant implications for managers in the IT sector. Furthermore, limitations and future directions are discussed, addressing the issues of vitality and job performance based on gender.